Efektivitas Pelayanan Publik Bagi Pasien Pengguna BPJS di RSUD dr. M. Soewandhie Kota Surabaya - Gabriela Zera Theofani; Dwi Retno Oktaviani; Berlian Surya Maharani; Prizalia Berliana Putri; Shafira Zahra Almadea; Binti Azizatun nafi’ah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
A survey conducted by the Ombudsman of the Republic of Indonesia indicates that public services in Indonesia are still unsatisfactory, particularly in the healthcare sector, which is one of the basic rights of the community. Through the Social Security Administering Body (BPJS) program, the government strives to provide social security to the public, including access to quality healthcare services. However, there are still challenges in the effectiveness of public services, especially in the context of hospitals. A surprise inspection by the Mayor of Surabaya at the Dr. Mohamad Soewandhie Regional General Hospital revealed several deficiencies in service, which were subsequently addressed by the hospital with various improvements, including increased efficiency and the use of technology. Therefore, this study aims to explore the effectiveness of public services for BPJS patients at Dr. Mohamad Soewandhie Regional General Hospital in Surabaya, with the hope of providing deeper insights into the performance of public services in government institutions. This research uses qualitative research techniques with a descriptive strategy. The location of the study is Dr. Soewandhie Regional General Hospital in Surabaya. Based on our observations and interviews with various parties, we determined that the services provided by Dr. Soewandhie Regional General Hospital to BPJS Kesehatan patients have successfully achieved the main goals of the program, namely providing adequate and quality infrastructure, facilities, and healthcare services for patients. However, there are challenges such as the renewal of BPJS accounts that have expired.